Evaluation of Blended Learning Implementation in Faculty of Teacher Training and Education, Universitas Lampung - Sowiyah, Sowiyah (Jurnal Pendidikan Progresif, 2020)
Evaluation of Blended Learning Implementation in Faculty of Teacher Training and Education, Universitas Lampung. Objectives: This study aims to evaluate the implementation of an online blended learning namely Edusmart as a support for face-to-face lectures at the Faculty of Teacher Training and Education, Universitas Lampung (FKIP UNILA). Methods: This study used a qualitative descriptive research method using three instruments, namely the observation guidelines, interviews and questionnaires. The subjects in this study were lecturers, students and helpdesk admin in FKIP UNILA. Data were collected in accordance with the object of research, namely to describe the implementation of blended learning through observation, interviews and questionnaires related to the responses of lecturers and students. Findings: The results showed that the implementation of blended learning had a positive impact and received good responses from lecturers and students. Students and lecturers are actively involved in learning activities, both online and face-to-face.Keywords: evaluation, implementation, blended learning DOI: http://dx.doi.org/10.23960/jpp.v10.i3.202005